PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum MILL.) PADA PEMBERIAN PUPUK ZN DAN JARAK TANAM YANG BERBEDA - Alvera Prihatini Dewi Nazari; Rusdiansyah Rusdiansyah; Ary Puja Meklin Siregar; Abdul Rahmi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2020)
Tomato (Lycopersicum esculentum Mill.) is a plant that is rich in benefits, but the yield is still low, some of which are due to a lack of nutrients, one of which is micro nutrient zinc, and improper plant spacing. The research was carried out to determine: 1) the best dose of Zn fertilizer and the right plant spacing; 2) the interaction between Zn fertilizer dosage and plant spacing; 3) the relationship (correlation) between the two observed variables. The research was conducted from July to October 2018 in Teluk Dalam Village, Mulawarman Village, Tenggarong Seberang District, Kutai Kartanegara Regency. The 4x3 factorial experiment was arranged in a Randomized Complete Block Design with three replications. The first factor was the dose of Zn fertilizer, consisting of four levels, namely 0.00; 3.00; 6.00; and 9.00 kg Zn ha-1. The second factor was plant spacing, consisting of: 50 cm x 50 cm; 60 cm x 50 cm; 70 cm x 50 cm. Data were analyzed using analysis of variance, followed by the LSD test at the 5% level. Correlation analysis was used to determine the relationship between two quantitative variables. The results showed that the effect of Zn fertilizer dosage was significantly different on plant height and plant age at first harvest, number of fruit per plant, fruit fresh weight per plant, harvest frequency, and fruit fresh weight per hectare, but not significantly different on plant height and age plants at flowering and the number of branches per plant. The effect of plant spacing was significantly different, on the other hand, the interaction was not significantly different on all observed variables.  The best dose of Zn fertilizer is 6.00 kg ha-1 with fruit fresh weight 25.16 Mg ha-1 and the best plant spacing is 70 cm x 50 cm  with fruit fresh weight 25.18 Mg ha-1.  The results of the correlation analysis showed that fruit fresh weight per hectare had a positive correlation with the number of fruit, fruit fresh weight per plant, and the frequency of harvest with the correlation coefficient (r), respectively 0.7350; 0.8190; and 0.6316, but negatively correlated with plant age at flowering and first harvest, namely -0.2552 and -0.3292.